2020
DOI: 10.3389/fpls.2020.00067
|View full text |Cite
|
Sign up to set email alerts
|

Combined Silicon-Phosphorus Fertilization Affects the Biomass and Phytolith Stock of Rice Plants

Abstract: Phytoliths are silica bodies formed in living plant tissues. Once deposited in soils through plant debris, they can readily dissolve and then increase the fluxes of silicon (Si) toward plants and/or watersheds. These fluxes enhance Si ecological services in agricultural and marine ecosystems through their impact on plant health and carbon fixation by diatoms, respectively. Fertilization increases crop biomass through the supply of plant nutrients, and thus may enhance Si accumulation in plant biomass. Si and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…SiF can significantly increase the available Si content in soils and thus the plant organs of Moso bamboo forests, which can promote the formation of phytolith since Si is an important component in phytolith. This pattern is in accordance with a recent study (Li et al, 2020b) that has showed that the addition of SiF can increase available Si in soil.…”
Section: Effects Of Different Management Measures On the Accumulationsupporting
confidence: 93%
“…SiF can significantly increase the available Si content in soils and thus the plant organs of Moso bamboo forests, which can promote the formation of phytolith since Si is an important component in phytolith. This pattern is in accordance with a recent study (Li et al, 2020b) that has showed that the addition of SiF can increase available Si in soil.…”
Section: Effects Of Different Management Measures On the Accumulationsupporting
confidence: 93%
“…Si extracted with CaCl 2 (Si CaCl2 ), acetate, acetic acid, or citrate are used as PAS proxies since the concentrations extracted by these reagents are proportional to plant Si concentration or grain yield 22 , 23 . PAS concentrations extracted by these reagents have been shown to be positively correlated with soil properties such as phytolith content 24 , pH 25 27 , < 2 µm fraction 7 , 28 , organic matter, and iron oxides 28 . A negative correlation between PAS and total Si content has also been documented, reflecting the predominance of low solubility minerals such as quartz in the Si pool 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This adverse effect on the ions-utilizing system alters the biochemical and metabolic processes of plants when the intake of Na + exceeds its efflux through the plasma membrane channels [ 6 ]. The ionic system in plants has been reported to be extensively linked to the ideal concentration of phosphorus and silicon [ 7 ] Bargaz et al [ 8 ] reported that phosphorus (P) supplies induced salt tolerance in Phaseolus vulgaris through acquisition of K + and Ca ++ . Similarly, several literature studies have reported the role of silicon (Si) in improving plant physiology, growth, and yield [ 9 ].…”
Section: Introductionmentioning
confidence: 99%